PERANCANGAN KAMPANYE SOSIAL DAMPAK GAME ONLINE BAGI REMAJA DI KOTA PALEMBANG - Junoko, Safar; Yulius, Yosef; Prasetya, Didiek (Besaung : Jurnal Seni Desain dan Budaya)
Technological progress is something that can not be avoided in today's life. One of the results of technological development is the internet, one of its benefits is as a means of entertainment, for example to play online games. Online games themselves are not only played from computer games but can also be played on smartphones, online games are much loved by teenagers because online games themselves are a means of entertainment for them but most teenagers are addicted to playing online games. Online games themselves have positive and negative impacts, but if playing excessive online games can have positive impacts which are definitely addicted to playing continuously. The main study of this research focuses on the identification, analysis and design of Video Motion Graphic works and other supporting media. This design uses premedia media planning methods, playing media and media follow-up. Data collected through, observation, interviews, literature and website. The data is then identified, classified, selected, then analyzed using the 5W + 1H method and interpreted according to the text and context. The design of the social media campaign of the impact of online games for teens in the city of Palembang as a visual communication media which is part of the design discussion. This design aims to encourage adolescents to reduce and reduce the number of addictions due to online games especially teenagers in the city of Palembang in order to be able to balance between playing online games and learning to get achievements in education.